(untitled) (Al-Mukhtar Journal of Legal Science, 2025)
Providing humanitarian assistance in the event of natural disasters is a fundamental right for the victims of these disasters، and a necessary duty that requires providing everything necessary to confront them and address the effects that the state finds difficult to address alone، regardless of its capabilities. The right to receive humanitarian assistance is closely linked to other human rights، and its recognition is a result of the implementation of these rights، as it represents the basic guarantee for the enjoyment of human rights in the event of crises and disasters. Given the urgent need to obtain assistance resulting from this exceptional circumstance، and to ensure that the provision of humanitarian assistance in the event of natural disasters does not affect the sovereignty and territorial integrity of the affected state، the provision of humanitarian assistance is regulated by a set of principles that must be adhered to while performing this humanitarian duty.